Self-Service Technology Berbasis Android Menggunakan RestFul Web Service Pada Bisnis Restoran - Yoseph Halim; Sandy Kosasi; Tony Wijaya; Susanti M. Kuway (Indonesian Society of Applied Science, 2021)
The process of ordering food and beverage menus at the Meatzilla restaurant still uses paper and stationery. Constraints that are often encountered are when restaurant visitors are crowded, but waiters are limited, often mistaken of orders and loss and order of paper orders and various other obstacles. This can cause feelings of disappointment and negative impressions which will certainly result in reduced customer satisfaction. This study aims to produce mobile device software that can support the running of food and beverage ordering systems at Meatzilla Restaurant self-service so that orders arrive quickly and right desires. This system is made using XML and java programming language with android studio tools version 3.5.3. Research in the form of case studies, software design methods using extreme programming models and system modeling tools using Unified Modeling Language (UML). This system is connected to the internet network where the admin, cashier, kitchen and customers are integrated with a restful web service. The final result of this study is a food and beverage ordering system consisting of 4 (four) parts, namely customer and admin software that is accessed by using a smartphone and the cashier and kitchen which is accessed by a PC / laptop. this system is very helpful in facilitating the management of customer orders.